THE EFFECT OF WORK EXPERIENCE, INTEGRITY, AND COMPETENCE OF AUDITORS ON AUDIT QUALITY WITH EMOTIONAL INTELLIGENCE AS A MODERATING VARIABLE (Case Study on BPKP South Sulawesi Province) - Andi Hardianti; Alimuddin; Syamsuddin (International Journal of Social Science, 2022)
This study aims to analyze the effect of auditor's work experience, integrity and competence of auditors on audit quality at the Office of the Financial and Development Supervisory Agency Representative for South Sulawesi Province. With emotional intelligence as a moderating variable. This study uses moderated regression analysis (MRA) using the SPSS Version 28 application. The results of the analysis show that the variables that have a direct effect on audit quality and fulfill significant assumptions are: Auditor work experience and auditor integrity. while auditor competence has no significant effect on audit quality. Auditor work experience with a p value of 0.032 > 0.05, meaning that the higher the auditor's work experience (X1), the better the audit quality (Y) produced. Auditor integrity with p value 0.001 < 0.05, it means that the higher the auditor integrity (X2), the higher the audit quality (Y). auditor competence with p value 0.746 <0.05, meaning that auditor competence (X3) has no significant effect on audit quality (Y). The results of the moderating regression analysis for the effect of emotional intelligence (Z) in moderating the relationship between auditor's work experience (X1) on audit quality (Y) showed a probability value of 0.016 < 0.050. The value indicates that emotional intelligence has a positive and significant effect in moderating the relationship between auditor work experience and audit quality. The results of the regression analysis for the effect of emotional intelligence (Z) in moderating the relationship between auditor integrity (X2) and audit quality (Y) show a probability value of 0.010 < 0.050. This value indicates that emotional intelligence has a positive and significant effect in moderating the relationship between auditor integrity and audit quality. The results of the regression analysis for the effect of emotional intelligence (Z) in moderating the relationship between auditor competence (X3) on audit quality showed a probability value of 0.010 <0.050. The value indicates that emotional intelligence has a significant effect in moderating the relationship between auditor competence and audit quality.